3D-printed PEEK versus conventional free fibula flap for jaw reconstruction: a comparative clinical study - Feng, Dongdong; Zhang, Yuxiang; Guo, Haiwei; Zheng, Chuanming; Zhang, Yining; Zhang, Wanchen; Lai, Fangyuan; Xu, Jiajie (Frontiers in Oncology, 2025)
PurposeAimed to evaluate the application value of polyether ether ketone (PEEK) based on three-dimensional (3D) printing technology for jaw reconstruction.MethodsThis study retrospectively analyzed 16 patients who underwent jaw reconstruction in the Department of Head and Neck Surgery, Zhejiang Provincial People’s Hospital, from August 2019 to December 2023. A subsequent comparison was made between the effectiveness of free fibula flap (FFF) and PEEK schemes.ResultA total of 16 patients were included in this study. In the FFF group, six male and two female patients (mean age, 40.8 ± 21.2 years) underwent jaw defect reconstruction successfully. However, one patient in this group required the removal of the titanium plate due to uncontrollable infection. In the PEEK group, which consisted of five men and three women (mean age, 56.3 ± 12.6 years), six patients achieved satisfactory outcomes, including accurate jaw restoration and good occlusal function during follow-up, and were successfully discharged. However, two patients in this group experienced secondary infection, which necessitated the removal of the PEEK implants and subsequent salvage reconstruction using FFF. The operative time was significantly shorter in the PEEK group compared to the FFF group (p < 0.05). Infection was identified as the primary cause of reconstruction failure in the PEEK group, for which FFF served as an effective salvage procedure. Although the PEEK group showed lower means in intraoperative blood loss, postoperative drainage, and reduction in Body Mass Index (BMI) compared to the FFF group, these differences did not reach statistical significance.Conclusion3D printing technology enables the fabrication of patient-specific PEEK implants with customized geometries. Owing to its stable biocompatibility, PEEK is suitable for reconstructing complex and irregular jaw defects. As a viable alternative for primary jaw reconstruction, it demonstrates promising clinical application prospects.